Modelling the Repair of Carbon-Centered Protein Radicals by Phenolic Antioxidants - Max Walton-Raaby; Tyler Floen; Nelaine Mora-Diez (MDPI AG, 2024)
Oxidative stress is a biological process that has been linked to many diseases, hence understanding how to prevent and repair it is essential to medicine. The thermodynamics and kinetics of the repair reactions of radically damaged leucine (a lateral chain in a simplified protein environment) by twenty phenolic antioxidants are studied at the M06-2X(SMD)/6-31++G(d,p) level of theory in water and pentyl ethanoate. The two repair mechanisms modelled are formal-hydrogen atom transfer (f-HAT) and single electron transfer (SET). Although all f-HAT reactions are thermodynamically favourable, only one of the phenols produced rate constants in the diffusion limit, exhibiting biological relevance. SET is not suspected to be an important repair pathway for the phenols studied. We show that the Bell-Evans-Polanyi principle, which relates thermodynamics and kinetics properties for a reaction, breaks down when comparing between the solvents, protein repair sites, and the phenolic antioxidants. While thermodynamic data can be used as valuable screening tools, the kinetic calculation of rate constants in solution is crucial for enhancing the biological relevance of theoretical studies.